-2(x+1)=2(-3x+1)

Simple and best practice solution for -2(x+1)=2(-3x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(x+1)=2(-3x+1) equation:


Simplifying
-2(x + 1) = 2(-3x + 1)

Reorder the terms:
-2(1 + x) = 2(-3x + 1)
(1 * -2 + x * -2) = 2(-3x + 1)
(-2 + -2x) = 2(-3x + 1)

Reorder the terms:
-2 + -2x = 2(1 + -3x)
-2 + -2x = (1 * 2 + -3x * 2)
-2 + -2x = (2 + -6x)

Solving
-2 + -2x = 2 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-2 + -2x + 6x = 2 + -6x + 6x

Combine like terms: -2x + 6x = 4x
-2 + 4x = 2 + -6x + 6x

Combine like terms: -6x + 6x = 0
-2 + 4x = 2 + 0
-2 + 4x = 2

Add '2' to each side of the equation.
-2 + 2 + 4x = 2 + 2

Combine like terms: -2 + 2 = 0
0 + 4x = 2 + 2
4x = 2 + 2

Combine like terms: 2 + 2 = 4
4x = 4

Divide each side by '4'.
x = 1

Simplifying
x = 1

See similar equations:

| (6x-5)+3x=90 | | 3z+7=112+z | | (4m+7)(2m-12)=0 | | 4(y+1)=5+-21 | | x-3.428571=0.66 | | 6+4w=16 | | s^2-7s=-19 | | 5x-4=-2x-3 | | 4X=18whatsx | | (3x+8)*x=360 | | 18-12+4w=16 | | 42x-300x-288=0 | | (4x+3y)dx+(2y-3x)dy=0 | | 5x-4=-2-3 | | 2j^2-3j+1=o | | m^2-19m=-88 | | -5y+4(2y-7)=-37 | | 3(x+5)-4(2x+3)=-5+9 | | x=(x-1)20 | | 0=-3x^2+4x-5 | | 5/0.2 | | (3x+2)(3x^2-19x+20)=0 | | 4s+2=3s-10 | | n^2-6n-54=-54 | | u/12=17/11 | | 4q+-12=2q-2 | | 2n+3n=45 | | z^2-2z-17=7 | | 9(10+x)=36 | | f(-x)=3x^2+2x+6 | | 16=(x-y)*4 | | (-7U^2+2U-4)+(3u^2+5U+6)=U |

Equations solver categories